SYSTEM DESIGN OF THE POSITION IN FUNCTIONAL PELINDO II JAKARTA RESEARCHER - Muhammad Guntur; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2000)
The duration of accessing information due to work on the running system is done manually. If this proposed new system is already running, then the constraints faced can be resolved. This proposed system Kuga will be able to provide information in a relatively quick time, generate reports more easily, and can search the data back if required.